SOCIAL MEDIA IN A CONTENT COURSE FOR THE DIGITAL NATIVES - Anita Lie (TEFLIN, 2013)
Digital technologies and the Internet have revolutionized the way people gather information and acquire new knowledge. With a click of a buttonor a touch on the screen, any person who is wired to the internet can access a wealth of information, ranging from books, poems, articles, graphics, animations and so much more. It is imperative that educational systems and classroom practices must change to serve our 21st century students better.Â This study examines the use of Edmodo as a social media to teach a course in Pedagogy to a class of digital natives. The media is used as an out-of-class communication forum to post/submit assignments and resources, discuss relevant issues, exchange information, and handle housekeeping purposes. A survey of studentsâ responses and discussions on their participatory process leads to insights on how the social media helps achieve the required competences.